1998
DOI: 10.1038/bjc.1998.333
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of hepatic steatosis by computerized tomography in patients receiving 5-fluorouracil-based therapy for advanced colorectal cancer

Abstract: Summary The frequency and severity of fatty infiltration of the liver in patients receiving 5-fluorouracil (5-FU) and folinic acid has not been documented systematically. Its development can result in difficulty assessing disease progression, and treatment may be altered inappropriately. Twenty-seven patients with colon cancer and liver metastases receiving 5-FU and folinic acid were studied with computerized tomography (CT) before treatment and after six or 12 cycles of chemotherapy. Forty-seven per cent of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
1
6

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(91 citation statements)
references
References 8 publications
2
79
1
6
Order By: Relevance
“…The addition of bevacizumab has been associated with a lower incidence of oxaliplatin-induced SOS and NRH lesions [116]. Similarly, irinotecan has been linked to the development of steatohepatitis, a type of nonalcoholic fatty liver disease [117,118], and 5-FU plus leucovorin and/or irinotecan are associated with a higher incidence of hepatic steatosis, particularly in patients with a body mass index Ͼ25 kg/m 2 [119,120]. Many patients with liver metastases from CRC are only referred for surgical resection following numerous prior chemotherapy regimens, but accumulated hepatic toxicity may mean that curative surgery is no longer possible in some of these patients, highlighting the importance of coordinated efforts among medical oncologists, surgeons, and patients to optimize disease management [121].…”
Section: Pathological Responsementioning
confidence: 99%
“…The addition of bevacizumab has been associated with a lower incidence of oxaliplatin-induced SOS and NRH lesions [116]. Similarly, irinotecan has been linked to the development of steatohepatitis, a type of nonalcoholic fatty liver disease [117,118], and 5-FU plus leucovorin and/or irinotecan are associated with a higher incidence of hepatic steatosis, particularly in patients with a body mass index Ͼ25 kg/m 2 [119,120]. Many patients with liver metastases from CRC are only referred for surgical resection following numerous prior chemotherapy regimens, but accumulated hepatic toxicity may mean that curative surgery is no longer possible in some of these patients, highlighting the importance of coordinated efforts among medical oncologists, surgeons, and patients to optimize disease management [121].…”
Section: Pathological Responsementioning
confidence: 99%
“…An important observation in our study was that 5-FU treatment induced a significant triglyceride accumulation in hepatocytes and HepG2 cells, an incidence known from clinical trials, where up to half of patients receiving 5-FU monotherapy were found to develop hepatic steatosis [14][15][16][17]. One factor contributing to hepatocellular lipid accumulation is endogenous de novo lipogenesis [49,50].…”
Section: Discussionmentioning
confidence: 62%
“…With the continued rise of obesity in the Western countries, the prevalence of NAFLD has followed a similar trend and is today recognized as the most common liver disease worldwide [18,19]. NAFLD is characterized by hepatic steatosis, which is also the most documented liver pathology observed in association with 5-FU administration [14,16,17,20]. In general, hepatic steatosis is characterized by intravesicular accumulation of fat in the form of triglycerides within hepatocytes [18,19].…”
Section: Research Papermentioning
confidence: 98%
See 1 more Smart Citation
“…Chemotherapy can also result in steatosis of the liver [39,46]. The ability of noninvasive imaging studies to evaluate steatotic livers continues to evolve [47, 48 • ].…”
Section: Hepatic Steatosismentioning
confidence: 99%